Bioassay-guided profiling of quercus infectoria gall extracts using hplc and their antimalarial activity - Hamidon, Nurul Hammizah (2025)
Malaria is a public health concern as the emergence of drug-resistant malaria parasites causes significant morbidity and mortality annually. The discovery of potent antimalarial drugs derived from medicinal plants is believed to be a crucial strategy for addressing the antimalarial drug resistance crisis. Therefore, the antimalarial properties of crude extracts from Quercus infectoria (QI) galls were investigated through bioassay-guided fractionation. Acetone (QIA) and methanol (QIM) crude extracts have been reported to exhibit promising antimalarial activity against Plasmodium falciparum (3D7 strain) with IC50 values of 5.85 ± 1.64 μg/mL and 10.31 ± 1.90 μg/mL, respectively. These extracts were subjected to fractionation using automated preparative high-performance liquid chromatography (prep-HPLC) to identify the most active fractions. Nine fractions were separated from each extract, of which the fractions QIA6 and QIM6 showed potent antimalarial activity, with IC50 values of 17.65 ± 1.82 μg/mL and 24.21 ± 1.88 μg/mL, respectively. In comparison, the standard antimalarial drug artemisinin had an IC50 value of 0.004 ± 0.001 μg/mL. The fractions of the Quercus infectoria galls exhibited antimalarial activity, which could be attributed to the presence of various secondary metabolites, particularly phenolic compounds such as ellagic acid. The high-performance liquid chromatography (HPLC) analytical method was established for the quantification of ellagic acid as a marker in the Quercus infectoria gall crude extract. All parameters including specificity, precision, accuracy, linearity, limit of detection (LOD) and limit of quantitation (LOQ), were found to be in the acceptable criteria of the ICH guideline. Targeted phenolic compound analysis of the most active fraction was performed by high-resolution liquid chromatography coupled with mass spectrometry (HR-LCMS). HR-LCMS analysis was conducted on the active fractions, QIA6 and QIM6, and revealed that kaempferol-3-O-glucoside, quercetin-3-glucoside, and syringic acid were among the major compounds identified in QIA6, while syringic acid and 3,4-dihydroxybenzoic acid were predominant in QIM6. The correlation between antimalarial activity and phenolic compounds in fractions QIA6 and QIM6 led to the quantitation of four targeted phenolic compounds. Thus, this study showed promising antimalarial activity of Quercus infectoria (QI) galls when fractionation was performed, which can be used as a guideline for future investigations on the molecular mechanism underlying the antimalarial action and further reflect the importance of an in-depth antimalarial investigation.